PENGARUH PROFITABILITAS, LEVERAGE, FIRM SIZE, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS - Andrew Jaya Saputra, Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to obtain empirical evidence about the effects of profitability, leverage, firm size, and sales growth on financial distress in manufacturing industries listed in Indonesian Stock Exchange during the period of 2015-2017. This research used 109 samples of manufacturing companies that have been previously selected using purposive sampling method for three years. The data used were secondary data in the form offinancial information from the financial statements and annual reports. This research data was processed using E Views 9. The result of this research shows that profitability has a significant effect on financial distress, while leverage, firm size, and sales growth does not have a significant effect on financial distress. Suggestions that can be given is for further research, it is expected to use other independent variables such as liquidity, managerial ownership, or with good corporate governance that might show better results.